WYPOWIEDZI CYRYLA I W ZACHODNIOEUROPEJSKICH I POLSKICH MASSMEDIACH, CZYLI KOŚCIÓŁ PRAWOSŁAWNY W SŁUŻBIE PROPAGANDY WOJENNEJ W OBLICZU AGRESJI ROSJI NA UKRAINĘ (2022) - Owsiński, Piotr A. (Przegląd Wschodnioeuropejski, 2024)
Persuasion, disinformation and manipulation, which are a part of the propaganda, can be regarded as central terms of the language of politics especially during the conflict situations and wars. In the paper the problem is analyzed, in what way the language of politics uses the techniques of the propaganda in the official statements of Kirill in the context of the Russian invasion of Ukraine (2022). The explored corpus are the news announcements as well as the Kirill’s social media posts. The aim of such analysis is to examine, how and to what extent the Russian propaganda techniques through the agency of Kirill present and justify the war.